(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2021)
Abstract- Social media nowadays is among the ‘best possibilities available’ to an item to get in touch with potential customers. Community social networking websites are the method to interact socially. Social media is a phenomenon that has become an important aspect in marketing mix and revolutionizing the way companies interact with customers.These new media win the believe in of customers by linking with them at a deeper level. Community online marketing is the new mantra for several manufacturers since early a season ago. ref. 7 Promoters are considering many different social media possibilities and beginning to apply new social projects at a higher rate than ever before. Community online marketing and the companies that utilize it have become more sophisticated. One cannot afford to have no existence on the social programs if the competitor is creating waves with its solutions and items. The blast of social media trend is as amazing as that and the speed at which it is improving is frustrating.The findings presented in this study conclude that even though social media is more effective than some of the traditional advertising channels, it cannot be implemented in isolation without augmenting it with other forms of traditional advertising channels.